Dopamine disruption increases cleanerfish cooperative investment in novel client partners - Soares, Marta C. (R Soc Open Sci, 2017)
Social familiarization is a process of gaining knowledge that results from direct or indirect participation in social events. Cooperative exchanges are thought to be conditional upon familiarity with others. Indeed, individuals seem to prefer to engage with those that have previously interacted with them, which are more accurate predictors of reward than novel partners. On the other hand, highly social animals do seek novelty. Truth is that the physiological bases underlying how familiarity and novelty may affect cooperative decision-making are still rather obscure. Here, we provide the first experimental evidence that the level of the dopaminergic influence in cooperative exchanges is constrained to mechanisms of social familiarization and novelty in a cleanerfish, Labroides dimidiatus. Cleaners were tested against familiar and novel Ctenochaetus striatus surgeonfish (a common client species) in laboratorial conditions, and were found to spend more time providing physical contact (also referred to as tactile stimulation) to familiar fish clients. Cleaners use tactile stimulation as a way to reduce the risk of a non-rewarding outcome, a behavioural response that is even more pronounced when blocking dopamine (DA) D1 receptors. We discovered that the influence of DA disruption on cleaners' provision of physical contact was dependent on the level of familiarity with its partner, being highly exacerbated whenever the client is novel, and unnoticed when dealing with a familiar one. Our findings demonstrate that DA mediation influences the valuation of partner stimuli and the enhancing investment in novel partners, mechanisms that are similar to other vertebrates, including humans.